Design Optimization of the Multi-layer Switched Reluctance Motor to Minimize Torque Ripple and Maximize Average Torque - Payam Vahedi; Babak Ganji; Seyed Ebrahim Afjei (AUT Journal of Electrical Engineering)
Because of the high torque ripple of the switched reluctance motor (SRM), a novel design optimization method is introduced in the present paper for the multi-layer switched reluctance motor. Using this design optimization method, torque ripple is reduced significantly, and average torque is increased as well. In the proposed method, the significant reduction of torque ripple is derived from variation of both the motor geometric structure and the design/control parameters. The most important design parameters of the SRM that have a significant effect on the torque ripple and average torque of the motor are stator/rotor pole arcs. The optimal values of these parameters are determined here using the design of experiments (DOE) algorithm. Having the instantaneous torque waveform of the motor is necessary for the accurate calculation of torque ripple. In the present paper, this waveform is predicted using an analysis of the motor based on finite element method (FEM). Applying the introduced design optimization method to a typical 8/6 multi-layer SRM, simulation results are presented and the effectiveness of the proposed design optimization method is demonstrated. Since the produced average torque of the multi-layer SRM is higher than the conventional type of SRM (one-layer), the proposed design optimization procedure could be utilized appropriately for the construction of a high-power SRM with minimum torque ripple.